Green Analytical Method for Simultaneous Determination of Glucosamine and Calcium in Dietary Supplements by Capillary Electrophoresis with Capacitively Coupled Contactless Conductivity Detection - Yen Nhi Do; Thi Lan Phuong Kieu; Thi Huyen My Dang; Quang Huy Nguyen; Thu Hien Dang; Cao Son Tran; Anh Phuong Vu; Thi Trang Do; Thi Ngan Nguyen; Son Luong Dinh; Thi Minh Thu Nguyen; Thi Ngoc Mai Pham; et al. (Journal of Analytical Methods in Chemistry)
The need for analytical methods that are fast, affordable, and ecologically friendly is expanding. Because of its low solvent consumption, minimal waste production, and speedy analysis, capillary electrophoresis is considered a “green” choice among analytical separation methods. With these “green” features, we have utilized the capillary electrophoresis method with capacitively coupled contactless conductivity detection (CE-C4D) to simultaneously determine glucosamine and Ca2+ in dietary supplements. The CE analysis was performed in fused silica capillaries (50 μm inner diameter, 40 cm total length, 30 cm effective length), and the analytical time was around 5 min. After optimization, the CE conditions for selective determination of glucosamine and Ca2+ were obtained, including a 10 mM tris (hydroxymethyl) aminomethane/acetic acid (Tris/Ace) buffer of pH 5.0 as the background electrolyte; separation voltage of 20 kV; and hydrodynamic injection (siphoning) at 25 cm height for 30 s. The method illustrated good linearity over the concentration range of 5.00 to 200 mg/L of for glucosamine (R2 = 0.9994) and 1.00 to 100 mg/L for Ca2+ (R2 = 0.9994). Under the optimum conditions, the detection limit of glucosamine was 1.00 mg/L, while that of Ca2+ was 0.05 mg/L. The validated method successfully analyzed glucosamine and Ca2+ in seven dietary supplement samples. The measured concentrations were generally in line with the values of label claims and with cross-checking data from reference methods (HPLC and ICP-OES).